Brussels 1900 Vienna: Networks in Literature, Visual and Performing Arts, and other Cultural Practices - Defraeye, Piet; Mitterbauer, Helga; Reyns-Chikuma, Chris (Internationale Forschungen Zur Allgemeinen Und Vergleichenden Literaturwissenschaft, 2021)
Brussels 1900 Vienna examines the complex cultural networks between Austria and Belgium (1880-1930), and situates these interrelations within a wider European context. The collection covers various fields, including literature, translation, music, theatre, visual arts, café culture, and architecture.